Predictive Value of Diaphragmatic Ultrasonography for the Weaning Outcome in Mechanically Ventilated Children Aged 1–3 Years - Yao, Yelin; He, Liming; Chen, Weiming; Zhou, Hao; Lu, Guoping; Tao, Jinhao; Wang, SuJuan (Frontiers in Pediatrics, 2022)
Background: There are estimated 20% of mechanically ventilated patients having difficulty in weaning from the ventilators and the weaning process accounts for 40% of the whole ventilation time. Reliable tools are urgently needed to estimate the weaning outcome. Diaphragmatic ultrasonography, as a relatively good predictive method for the adults, was measured in this study assessing the value of each indicator of diaphragmatic ultrasonography to predict the outcomes of ventilator weaning from mechanically ventilated children of 1-3 years’ old. Methods: Between November 2018 and November 2019, children who were mechanically ventilated and ready for weaning in the pediatric intensive care unit (PICU) were enrolled in the study. Diaphragmatic ultrasonography was performed to the children for measuring and the right diaphragm excursion (DE), contraction velocity, thickness, and diaphragm thickening fraction (DTF) were recorded followed by spontaneous breathing trial (SBT). The receiver operator characteristic (ROC) curves were also used to assess the value of each indicator to predict the weaning outcome. Results: During this study period, a total of 72 children were enrolled, of them 56 children passed the weaning process and 16 children failed. There were significant differences in DE, contraction velocity, thickness, and DTF parameters between the weaning success group and the failure group. The areas under the ROC curves (AUC) and the optimal threshold of the above indicators were as follows: 0.72 and 8.08 mm for DE; 0.71 and 26.1% for right DTF (DTFR); 0.71 and 20.7% for left DTF (DTFL); 0.78 and 14.8% for minimum DTF (DTFMIN); 0.79 and 26.1% for maximum DTF (DTFMAX); 0.71 and 1.24 mm for maximum diaphragm thickness at the end of inspiration (DteiMAX); and 0.65 and 10.0 mm/s for contraction velocity. Conclusion: Diaphragmatic ultrasonography is feasible in guiding ventilator weaning and the indicators of DE, DTF and DteiMAX guide the weaning more accurately. Among them, DTF may act as a more reliable predictor of weaning by avoiding the influence of diaphragm development in children. (320 words)